Toll-like receptor 4 (TLR4) and typhoid fever in Vietnam. - Nguyen, T; Mai, N; Le, T; Ha, V; Nguyen, T; Tran, T; Nguyen, T; Farrar, J; Dunstan, S (2009)
Understanding the host genetic susceptibility to typhoid fever may provide a better understanding of pathogenesis and help in the development of new therapeutics and vaccines. Here we determine the genetic variation within the human TLR4 gene encoding the principal receptor for bacterial endotoxin recognition in typhoid fever patients. It is possible that genetic variants of TLR4 could detrimentally affect the innate immune response against S. typhi infection. Mutation detection and genotyping of TLR4 was performed on DNA from 414 Vietnamese typhoid fever patients and 372 population controls. dHPLC detected a total of 10 polymorphisms within the upstream and exonic regions of TLR4, of which 7 are novel. Two SNPs, T4025A and C4215G, were more frequent in typhoid cases than in controls however due to their low allele frequencies they showed borderline significance (T4025A: OR 1.9, 95%CI 0.9-4.3, P 0.07 and C4215G: OR 6.7, 95%CI 0.8-307, P 0.04). Six missense mutations were identified, with 5/6 positioned in the ectoplasmic domain. Four missense mutations and one promoter SNP (A-271G) were only present in typhoid cases, albeit at low allele frequencies. Here we determined the extent of genetic variation within TLR4 in a Vietnamese population and suggest that TLR4 may be involved in defense against typhoid fever in this population.